PSXII-7 In vitro ruminal and total tract digestibility of diets containing high inclusions of wet distillers grains for feedlot sheep - Almeida, Marco Túlio C (J Anim Sci, 2019)
The objective was to evaluate the effects of increasing inclusion of wet distillers grains (WDG) on in vitro ruminal and total tract digestibility in feedlot sheep. Three crossbred ruminally-cannulated male sheep were used as rumen liquid donor. Treatments consisted of isonitrogenous and isoenergetic diets, containing 0, 15, 30 or 45% WDG on DM basis (Control, 15WDG, 30WDG, and 45WDG, respectively). Diets were composed of sugarcane bagasse (20%) and the concentrate (80%) composed of soybean meal (except 45WDG), wheat meal, WDG (except Control), urea, limestone, and mineral-vitamin premix. In vitro digestibility of DM (IVDMD), NDF (IVNDFD), and CP (IVCPD) were performed using the Ankom-DaisyII fermenter. Ruminal digestibility was evaluated after 48h incubation (39°C) using twenty-five filter bags. After 48h, twelve filter bags remained into each jar to evaluate the total tract digestibility. For it, 40mL of 6N HCl and 8g of pepsin were added and incubated for another 24h. The post-ruminal digestibility was calculated by the difference between rumen and total tract digestibility. Data were analyzed using SAS software. Contrasts were used to determine the linear and quadratic effects of WDG inclusions, as well as the contrast Control × WDG treatments. The WDG inclusion linearly decreased the ruminal and total DM and CP digestibility and increased the post-rumen CP digestibility (P < 0.05). When all treatments with WDG were evaluated against the Control, a significant effect was observed for IVDMD, with averages of 68.86 × 77.38%, 5.60 × 0.77% and 71.41 × 78.20%, and for IVCPD, with averages of 68.89 × 95.27%, 21.30 × 1.99% and 90.15 × 97.27%, respectively for rumen, post-rumen and total tract digestibility (P < 0.05). The results indicate that inclusions of WDG at up to 45% in the diets for sheep reduce the ruminal and total DM utilization, however, promote a better post-rumen use of CP of diets.